Water sorption thermodynamics in poly(propylene sebacate). (5th August 2016) - Scherillo, Giuseppe; Carbone, Maria Giovanna Pastore; Petretta, Mauro; La Manna, Pietro; Panayiotou, Costas; Bikiaris, Dimitrios N.; Musto, Pellegrino; Mensitieri, Giuseppe
Abstract: Water sorption thermodynamics in poly-propylene sebacate, PPSeb, a biodegradable semi-crystalline polyester, has been studied above its glass transition temperature. Experimental results have been obtained by using gravimetric methods to determine water sorption isotherms at several temperatures, as well as by means of in-situ FTIR transmission spectroscopy, to obtain qualitative information and quantitative estimates on the self- and cross-Hydrogen Bonds occurring within the water-polymer mixture. In fact, the water-polymer system has been found to be populated by several water 'species', each one characterized by a particular configuration of HB interactions. Different moieties on the polymer backbone are involved in the formation of specific interactions. The experimental results have been interpreted in the light of the Non Random Hydrogen Bonding (NRHB) lattice fluid theory for mixtures, which accounts both for the presence of Hydrogen Bonding (HB) interactions and for non randomness of the lattice contacts. An excellent fitting of experimental water sorption isotherms has been obtained, from which relevant mean-field and HB interactional parameters of the model have been calculated. On that basis, NRHB model has been then used to obtain qualitative and quantitative predictions, at equilibrium, of self and cross HB interactions involving both water molecules and groups present on the macromolecules within the polymer-water mixture, which compare well with the experimental results of FTIR spectroscopy. Graphical abstract: Highlights: Modeling water sorption thermodynamics in polypropylene sebacate. Quantification of different water species by vibrational spectroscopy. Identification of interacting sites on polymer backbone. Quantitative evaluation of hydrogen bonds in polypropylene sebacate-water systems. Reliability of theoretical results tested vs. in situ FTIR spectroscopy experiments.